Long-term outcome after surgical treatment of a congenital flexor tendon deformity in a pony - Salci, Hakan; Çelimli, Nureddin; Ayalp, Göksen Çeçen; Çalışkan, Ülke G. (Ferdowsi University of Mashhad, 2020)
Equine congenital or acquired flexor tendon deformity can occur immediately after birth or at any stage in the first 24 months of life. The long term prognosis after treating a severe flexor tendon deformity in horses may be poor. Although unfavorable prognosis of flexion deformities is a concept, but results of this presented case reveals that performing an appropriate treatment without any complications, will result in a functional improvement even in older patients, such as in this very case. The aim of this report is to present the long-term outcomes after the surgical treatment and  postoperative supports of a congenital flexor tendon deformity in a pony.
Keywords: tenotomy; pony; Veterinary medicine; SF600-1100; limb deformities; congenital